The effectiveness of therapeutic group and behavior for illogical belief and quality of peoples life related - Akram Dastjani, F; Mohammad Ali Rahmani; Taher Tizdast (Drug Control Headquarters, Research and Education Office, 2014)
Objective: This research with purpose of impression of recognition-manner group iatrical is done on change to invertebrate extinct beliefs and person`s life quality related to amphetamine. Method: thus have inspected 127 reference diseased to matters abusing iatrical centers of Arak city with questionnaire help of Jonz invertebrate extinguish (with 0.71 cronbakh alpha of persons to high marks) and life quality questionnaire (with 0.7 cronbakh alpha of persons to low marks). Then selected 30 diseased as situations possessing and holding and they reset to random replacing in two groups of examination and control (15 bodies in every group). So the method of recognition-manner group iatrical applied on examination group and the end again both groups have assessment with mentioned questionnaires. Obtained information of questionnaires, have been analysis through multi-parameter covariance analysis test. The obtains shown to difference of marks and scours of recognition-manner group iatrical is meaning in comparison to control group on reducing invertebrate extinct beliefs and increasing of person's life quality related to amphetamine. The results of the research shown that recognition-manner group iatrical is effective to management to parameters of invertebrate extinct beliefs and person' life quality related to amphetamine.